E-commerce Love Story: Bagaimana Skintific Menaklukkan Hati Gen Z dan Mengubah Keputusan Pembelian - Lina Parlina; Harto, Budi; Dewi Reniawaty; Rosliana Marsya Anggraeni (Program Studi Administrasi Bisnis, 2024)
One of the most effective marketing tools in the digital age is E-Commerce, especially when it comes to influencing Generation Z's inclination towards technology and social media. Skintific, merek produk kulit, and use digital marketing strategies like influencer marketing and social media to draw attention to this group. This study, which included 100 respondents, used a quantitative approach using a questionnaire to assess the impact of e-commerce strategy on customer satisfaction. The results show that e-commerce has a significant positive impact on consumer behavior with a regression coefficient of 0.605 and a contribution of 36.7%. Compared to traditional advertising, Gen Z is more responsive to relevant content, with Instagram and TikTok serving as the primary media. This highlights the importance of innovative digital marketing strategies in building strong relationships with Generation Z consumers and increasing sales in the worldwide market.